2019
DOI: 10.1242/jcs.234435
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct actin filament populations have effects on mitochondria, with differences in stimuli and assembly factors

Abstract: Recent studies show that mitochondria and actin filaments work together in two contexts: (1) increased cytoplasmic calcium induces cytoplasmic actin polymerization that stimulates mitochondrial fission and (2) mitochondrial depolarization causes actin assembly around mitochondria, with roles in mitophagy. It is unclear whether these two processes utilize similar actin assembly mechanisms. Here, we show that these are distinct actin assembly mechanisms in the acute phase after treatment (<10 min). Calcium-induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 67 publications
(110 reference statements)
2
26
0
Order By: Relevance
“…Several reports have shown that a cortical actin pattern is formed in differentiated keratinocytes 39,40 . Actin filaments are also known to be responsible for distributing organelles and mitochondrial depolarization [41][42][43] . Moreover, Gutowska-Owsiak et al showed that actin formed structures associated with filaggrin-containing keratohyalin granules and suggested that actin disruption accelerates keratinocyte differentiation programmes by filaggrin release from keratohyalin granules 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that a cortical actin pattern is formed in differentiated keratinocytes 39,40 . Actin filaments are also known to be responsible for distributing organelles and mitochondrial depolarization [41][42][43] . Moreover, Gutowska-Owsiak et al showed that actin formed structures associated with filaggrin-containing keratohyalin granules and suggested that actin disruption accelerates keratinocyte differentiation programmes by filaggrin release from keratohyalin granules 44 .…”
Section: Discussionmentioning
confidence: 99%
“…A rapid, dynamic and transient ‘burst’ in mitochondria-localized F-actin occurs within minutes (∼5 min) of damage and requires ARP2/3 ( Fig. 3 ), but is independent of INF2 and MYO6 ( Fung et al, 2019 ; Kruppa et al, 2018 ; Li et al, 2015 ). This leads to circularization of mitochondria, which is their last chance to recover before being committed to clearance by mitophagy.…”
Section: Mitochondrial Turnover and Quality Controlmentioning
confidence: 99%
“…Finally, dynamic assembly and disassembly of actin filaments onto mitochondrial subpopulations has been observed at ER–mitochondria contact sites; this is blocked by inhibition of actin nucleators, such as the ARP2/3 complex and formins ( Moore et al, 2016 ). This cycling is suggested to act as a steady-state surveillance method to modulate the mitochondrial fission–fusion balance to promote network remodelling and content mixing ( Fung et al, 2019 ; Moore et al, 2016 ).…”
Section: Mitochondrial Dynamics: Fission and Fusionmentioning
confidence: 99%
“…This process is governed by the mitochondrial protein mitochondrial Rho GTPase 1 (Miro1), a transmembrane protein consisting of two GTPase domains and two EF-hands, EF1 and EF2 (helix-loop-helix structural domain found in calcium-binding proteins) [ 27 ]. A recent study found that the distinct mechanisms regulating actin polymerization and depolarization are temporally associated with MiST [ 28 , 29 ]. Moreover, mitochondrial morphology and dynamics are partially regulated by the ER membrane contact sites (MCSs).…”
Section: Mitochondrial Remodeling In Cardiac Diseasesmentioning
confidence: 99%